Increasing Students' Learning Motivation Through the Utilization of the Quizizz Application in Learning - Lisa Yunita (JURNAL SOCIUS, 2026)
Learning motivation is one of the important factors that determine the success of the learning process. However, low student motivation to learn is still a problem that is often found at various levels of education, especially in learning that is still dominated by conventional methods and does not utilize interactive learning media. Therefore, technology-based learning innovations are needed that are able to increase student engagement and enthusiasm, one of which is through the Quizizz application. This study aims to analyze the effect of the use of the Quizizz application on student learning motivation based on the results of the research that has been published. The research uses  a literature review method  by examining various scientific articles, proceedings, and relevant academic sources regarding the use of Quizizz in learning. The data analysis technique is carried out using content analysis through the process of identifying, selecting, grouping, and synthesizing findings from various literature that meet the inclusion criteria. The results of the study show that the use of Quizizz has a positive influence on students' motivation to learn. The use of interactive quiz features, live feedback, ranking systems, and gamification elements can increase students' interest, active participation, confidence, and enthusiasm during the learning process. In addition, Quizizz creates a more fun, competitive, and collaborative learning atmosphere that encourages increased student engagement in learning activities. Thus, Quizizz can be used as an effective alternative digital learning media to increase student learning motivation at various levels of education.